PEOT/PBT Polymeric Pastes to Fabricate Additive Manufactured Scaffolds for Tissue Engineering - Higuera, Gustavo A.; Ramos, Tiago; Gloria, Antonio; Ambrosio, Luigi; Di Luca, Andrea; Pechkov, Nicholas; de Wijn, Joost R.; van Blitterswijk, Clemens A.; Moroni, Lorenzo (Frontiers in Bioengineering and Biotechnology, 2021)
The advantages of additive manufactured scaffolds, as custom-shaped structures with a completely interconnected and accessible pore network, are nowadays well established in tissue engineering. Pore volume and architecture can be designed in a controlled fashion, resulting in a modulation of scaffold’s mechanical properties and in an optimal nutrient perfusion determinant for cell survival. However, the success of an engineered tissue architecture is often linked to its surface properties as well. The aim of this study was to create a family of polymeric pastes comprised of PEOT/PBT microspheres and of a second biocompatible polymeric phase acting as a binder. By combining microspheres with additive manufacturing technologies, we produced 3D scaffolds possessing a tailorable surface roughness, which resulted in improved cell adhesion and increased metabolic activity. Furthermore, these scaffolds may offer the potential to act as drug delivery systems to steer tissue regeneration.